Association of Helicobacter pylori with lichen planus - Moravvej Hamideh; Hoseini Homa; Barikbin Behrooz; Malekzadeh Reza; Razavi Gita (Wolters Kluwer Medknow Publications, 2007)
Background : Lichen planus (LP) is a common idiopathic, inflammatory disorder that affects the skin, mucous membranes, nails and hair. Clinical observations and anecdotal reports have suggested a relationship between the exposure to a number of exogenous agents and the development of LP. One of the most important suggested bacterial etiologies is Helicobacter pylori (HP), that is one of the most common bacterial infections in the world, which is also reported to be common in Iran. Objective : This study was performed to evaluate the relation between HP and LP. Materials and Methods: A case control study was conducted with 80 patients with LP to find out a previous history of HP and 80 patients with other skin diseases were examined with urea breath test (UBT) as controls. Results: Sixty-six patients with LP and 49 patients from the controls had positive UBT. There was a significant difference about UBT positive result between these two groups. Conclusion: According to study, these results support a definitive etiological role for HP in LP.